Pengaruh Perencanaan Serta Pelaksanaan Dan Penatausahaan Terhadap Pertanggungjawaban Keuangan BUMDESA di Kabupaten Bengkalis - Teguh Widodo; Suharyono Suharyono (At-Tadbir : jurnal ilmiah manajemen, 2021)
This study aims to determine the effect of planning (X1), implementation and administration (X2) variables on accountability (Y). The object of this research is BUMDes in Bengkalis Regency, Riau. The method of determining the sample in this study using purposive sampling with a total sample of 32 BUMDes. The results of the study prove that the planning (X1), implementation and administration (X2) variables for accountability (Y) are partially or simultaneously. This proves that in BUMDes management, planning and implementation as well as administration in accordance with regulations and standard operating procedures will have an impact on optimal BUMDes management accountability.Keywords: Planning, Implementation, Administration, Accountability, BUMDes.